Analysis of the Areca Nut Agroindustry Value Chain in Padang Pariaman Regency - Saputra, Idil; Santosa; Hasbullah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
There are two chain structures consisting of main actors and supporting actors. The structure of the first chain is Farmers ? Small Collectors, ? Large Collectors ? Exporters. At the same time, the second chain structure is: Farmers, ? Home Industry, ? Collecting agents. Areca farmers get an added value of IDR 1,647.12/kilogram with an added value ratio of 71.80%. Small collectors get an added IDR 994.46/kilogram with an added value ratio of 22.10%. Prominent collectors get an added value of IDR 702.67/kg with a value-added ratio of 13.01%. The home industry obtains an added value of IDR 16,634.07/kilogram with an added value ratio of 79.21%. Farmers get a marketing margin of IDR 1,794.19/kilogram. Small collectors earn a marketing margin of IDR 1,500/kg. Collector traders earn a large marketing margin of IDR 900/kg. The home industry earns a marketing margin of IDR 18,000/kilogram.